A study in formulating resistance to change & organizational justice towards dimension of Learning Organization (LO) in private and public sector at Southern Region Malaysia / Siti Hamidah Mohd Nor - Mohd Nor, Siti Hamidah (2010)
The purposes of this paper are to develop a comprehensive understanding of how ‘learning organizations’ can be created and to provide a partial evaluation of the literature with a view to developing propositions for the future research agenda. To these ends, the paper analyzes the components of ‘learning organizations,’ deals with the barriers to organizational learning and several strategies for coping with them, draws upon the works of Senge a case of systems thinking, and then evaluates the ideas of main contributors of chaos and complexity theory from the managerial standpoint. In light of these intellectual constructs, the paper proposes a framework for managers in which the essential properties of complex systems that are capable of learning are set out. The paper also provides new propositions for future research. All 73 questions in this questionnaire evaluate the respondents in four sections which consist of the Demographic background, Learning Organization, Organizational Citizenship Behavior and also Organizational Commitment The result is in the form of reliability test, frequency, and also correlation. From the result that has been gathered, it shows that there is significant relationship between all the variables toward learning organization